The free movement of capital and foreign direct investment the scope of protection in EU Law - Hindelang, Steffen (Oxford : Oxford University Press, 2009)
This title offers a timely restatement of the EU law on free movement of capital, focusing on the effect of EU law on international investment. Through analysis of the complex case law, it sets out the rights enjoyed by investors under EU law.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Capital movements -- Law and legislation -- European Union countries